The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4184/asj.2017.11.6.892
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lumbosacral Transitional Vertebra in Individuals with Low Back Pain: Evaluation Using Plain Radiography and Magnetic Resonance Imaging

Abstract: Study DesignDescriptive cross-sectional study.PurposeTo determine the frequency of lumbosacral transitional vertebrae (LSTV) in patients with low back pain (LBP) and the role of iliolumbar ligament (ILL) origin from L5 in LSTV cases.Overview of LiteratureTransitional vertebrae are developmental variants of the spine. LSTV is a common congenital abnormality, and failure to recognize this anomaly may result in serious consequences during surgery.MethodsAll patients aged 11–90 years of either gender with LBP for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
2
9
1
1
Order By: Relevance
“…According to the results of our study, LSTV is quite common (9%). Previous studies have found higher percentages of LSTV (10.6-18.6%) [11][12][13][14][15][16][17]. Sacralisation was more common than lumbarisation, which is consistent with other studies (4.8% vs. 4.1%, respectively) [11,14].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…According to the results of our study, LSTV is quite common (9%). Previous studies have found higher percentages of LSTV (10.6-18.6%) [11][12][13][14][15][16][17]. Sacralisation was more common than lumbarisation, which is consistent with other studies (4.8% vs. 4.1%, respectively) [11,14].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous studies, the most common morphology of S1-2 intervertebral disc in the normal group was type 2 [17,19]. However, in some studies, the type 3 disc is most common in normal cases [20].…”
Section: O'driscoll Classificationsupporting
confidence: 86%
See 3 more Smart Citations